United Nations Declaration on the Rights of Indigenous Peoples: A Tool to Combat Inequalities Between Indigenous Peoples and the Globalized Society - ., Arnold Groh (2018)
In 2007, the General Assembly adopted the Declaration on the Rights of Indigenous Peoples with the majority of UN member states. The declaration is relevant to anyone in charge of or in contact with indigenous peoples. A central effect of the dominance of globalized culture over indigenous cultures is the asymmetry of perception and mutual influence. Due to the effects of the external social pressure of globalization, indigenous peoples have little freedom of choice. Exercising their right to cultural autonomy in education and lifestyle is very difficult for indigenous groups. On the part of governments, problems related to land rights are an obstacle to recognizing the autonomy of these peoples. Some of the analyzed articles of the United Nations Declaration on the rights of Indigenous People have relevance for external entities, such as groups of researchers or tourists, in contact with indigenous people.